Dietary intervention in the management of phenylketonuria: current perspectives - Rocha JC; MacDonald A (Dove Medical Press, 2016)
Júlio César Rocha,1-3 Anita MacDonald4 1Centro de Genética Médica, Centro Hospitalar do Porto – CHP, 2Faculdade de Ciências da Saúde, Universidade Fernando Pessoa, 3Center for Health Technology and Services Research (CINTESIS), Porto, Portugal; 4The Children’s Hospital, Birmingham, UK Abstract: Phenylketonuria (PKU) is a well-described inborn error of amino acid metabolism that has been treated for >60 years. Enzyme deficiency causes accumulation of phenylalanine (Phe) and if left untreated will lead to profound and irreversible intellectual disability in most children. Traditionally, it has been managed with a low-Phe diet supplemented with a Phe-free protein substitute although newer treatment options mainly in combination with diet are available for some subgroups of patients with PKU, for example, sapropterin, large neutral amino acids, and glycomacropeptide. The diet consists of three parts: 1) severe restriction of dietary Phe; 2) replacement of non-Phe L-amino acids with a protein substitute commonly supplemented with essential fatty acids and other micronutrients; and 3) low-protein foods from fruits, some vegetables, sugars, fats and oil, and special low-protein foods (SLPF). The prescription of diet is challenging for health professionals. The high-carbohydrate diet supplied by a limited range of foods may program food preferences and contribute to obesity in later life. Abnormal tasting and satiety-promoting protein substitutes are administered to coincide with peak appetite times to ensure their consumption, but this practice may impede appetite for other important foods. Intermittent dosing of micronutrients when combined with L-amino acid supplements may lead to their poor bioavailability. Much work is required on the ideal nutritional profiling for special SLPF and Phe-free L-amino acid supplements. Although non-diet treatments are being studied, it is important to continue to fully understand all the consequences of diet therapy as it is likely to remain the foundation of therapy for many years. Keywords: phenylalanine, PKU, L-amino acids, sapropterin, glycomacropeptide, large neutral amino acids